Peningkatan Hasil Belajar Menganalisis Surat Lamaran Kerja Siswa Kelas XII SMA Negeri 12 Palembang Menggunakan Model Jigsaw - Priyanto Priyanto (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
The results of learning to analyze the elements of student job applications, both from linguistic and structural elements, have not yet reached learning mastery. One way to overcome this is to apply the jigsaw learning model. For this reason, the purpose of this study was to describe the increase in learning outcomes by analyzing job applications for class XII students at SMA Negeri 12 Palembang using the jigsaw model. This type of research is classroom action research. The research was carried out with steps starting with pre-cycle, followed by cycle I with student success reaching 61.76% and ending with cycle II with completeness reaching 97.06%. Each cycle begins with planning, action, followed by observation and ends with reflection. The subjects of this study were 34 class XII students of SMA Negeri 12 Palembang, consisting of 12 male students and 22 female students. The research results up to cycle 2 show that students actively participate in the learning process analyzing job application letters and have achieved indicators of research success that have been set according to the completeness standards of Class XII SMA Negeri 12 Palembang, so this research is declared successful and complete with an average score of learning outcomes in cycle II of 82.40.